Analisis Faktor-Faktor Yangberhubungandengan Motivasi Petani Dalam Berusahatani Lada Di Kabupaten Aceh Besar - Zainuddin Zainuddin; Safrida Safrida; Elvira Iskandar (Fakultas Pertanian, Universitas Syiah Kuala, 2016)
ABSTRACTOne of the commodities that became the mainstay of Indonesia's exports is commodities pepper. In Indonesia, many pepper plants grown in the provinces of Lampung, Bangka, West Kalimantan and Aceh. Pepper plants in several regencies / cities in Aceh province. However, the development of commodity pepper planting area tends to decrease in almost every district. Aceh Besar district as a granary, pepper production in Aceh province also decreased acreage planting area. This condition is very contradictory because demand and prices of pepper are high but has not been used optimally. This is a reflection of the low motivation of farmers in pepper farming. The purpose of this study was to determine the level of motivation pepper farmers and determine the factors related to the motivation of farmers. The data analysis method used is Likert measurement scale systems and Spearman rank correlation. The data used are primary data time series period 2008-2013. Based on test results using a Likert scale of measurement that the level of motivation of farmers in pepper farming in Aceh Besar district in the high category. Based on the factors that have been tested using Spearman rank correlation, it is known that factors related to the level of motivation of farmers in pepper farming is the motivation of farmers with the availability of inputs, farmers motivated by cosmopolitan nature of farmers, and the motivation of farmers by supporting institutions. While revenue and service agencies there are not to relation with the motivation of pepper farmers. Keywords: Pepper Farm, Farmer Motivation Levels, External Factors, Spearman Rank Correlation